2023
DOI: 10.5114/jhk/162965
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hip and Knee Biomechanics during Sidestep Cutting in Male Basketball Athletes with and without Anterior Cruciate Ligament Reconstruction

Pinyada Warathanagasame,
Prasert Sakulsriprasert,
Komsak Sinsurin
et al.

Abstract: This study aimed to compare hip and knee biomechanics during sidestep cutting on the operated and non-operated sides in individuals with anterior cruciate ligament reconstruction (ACLR), and in an uninjured control group. Twenty male basketball athletes, 10 individuals with ACLR and 10 controls, were recruited. Hip and knee joint angles and angular velocities were investigated with a three-dimensional motion analysis system, and ground reaction forces (GRF) along with moments were collected during the decelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is critical to retrain—or develop—proper muscle activation patterns, joint biomechanics, and proprioception after primary ACL reconstruction to facilitate return to sport and prevent secondary ACL injury. Previous studies have demonstrated that athletes have altered hip/knee biomechanics and attenuated postural stability after ACL reconstruction 55,56 . Moreover, diminished neuromuscular control of the hip, knee, and ankle during landing and balancing tasks is predictive of a second ACL injury 57,58 .…”
Section: Prevention Of a Second Acl Injurymentioning
confidence: 99%
“…It is critical to retrain—or develop—proper muscle activation patterns, joint biomechanics, and proprioception after primary ACL reconstruction to facilitate return to sport and prevent secondary ACL injury. Previous studies have demonstrated that athletes have altered hip/knee biomechanics and attenuated postural stability after ACL reconstruction 55,56 . Moreover, diminished neuromuscular control of the hip, knee, and ankle during landing and balancing tasks is predictive of a second ACL injury 57,58 .…”
Section: Prevention Of a Second Acl Injurymentioning
confidence: 99%